Hallux valgus: a three-dimensional pathology. New therapeutic focus - Javier Yearson, Diego; Melendez, Ignacio; Anain, Federico; Siniscalchi, Santiago; Drago , Juan (Journal of the Foot & Ankle, 2021)
Objectives: To propose hallux valgus as a three-dimension disease and develop a surgical algorithm for each deformity pattern, incorporating the metatarsal rotation component. Methods: We prospective evaluated a series of 89 cases from February 2020 to February 2021, of which 80 were women and 9 were men. Mean age was 39 years and mean follow-up duration was 11.3 months. We used the Hardy-Clapham classification system and separated the patients into 2 groups: those with no rotational component (types 1 to 3), and those with a rotational componente (type 4 to 7). Results: Of the cases, 59% belonged to the first group and underwent distal chevron osteotomy, according to deformity degree on the frontal plane. The remaining 41% had a rotational component and underwent distal rotational chevron osteotomy, basal crescentic osteotomy, or modified Lapidus procedure, according to the degree of deformity in the frontal plane or associated instability. Union was achieved in all patients. Furthermore, mean American Orthopaedic Foot and Ankle Society score was 94.5 points, mean visual analog scale was 0.71, and level of satisfaction was 100%. Conclusion: By considering hallux valgus as a three-dimensional disease, we proposed a treatment protocol appropriate for each patient. Level of Evidence IV; Therapeutic Studies; Case Series.